Optimizing fungal DNA extraction and purification for Oxford Nanopore untargeted shotgun metagenomic sequencing from simulated hemoculture specimens - Nattapong Langsiri; Wieland Meyer; Laszlo Irinyi; Navaporn Worasilchai; Nuttapon Pombubpa; Thidathip Wongsurawat; Piroon Jenjaroenpun; J. Jennifer Luangsa-ard; Ariya Chindamporn (mSystems)
ABSTRACT Long-read metagenomics provides a promising alternative approach to fungal identification, circumventing methodological biases, associated with DNA amplification, which is a prerequisite for DNA barcoding/metabarcoding based on the primary fungal DNA barcode (Internal Transcribed Spacer (ITS) region). However, DNA extraction for long-read sequencing-based fungal identification poses a significant challenge, as obtaining long and intact fungal DNA is imperative. Comparing different lysis methods showed that chemical lysis with CTAB/SDS generated DNA from pure fungal cultures with high yields (ranging from 11.20 ± 0.17 µg to 22.99 ± 2.22 µg depending on the species) while preserving integrity. Evaluating the efficacy of human DNA depletion protocols demonstrated an 88.73% reduction in human reads and a 99.53% increase in fungal reads compared to the untreated yeast-spiked human blood control. Evaluation of the developed DNA extraction protocol on simulated clinical hemocultures revealed that the obtained DNA sequences exceed 10 kb in length, enabling a highly efficient sequencing run with over 80% active pores. The quality of the DNA, as indicated by the 260/280 and 260/230 ratios obtained from NanoDrop spectrophotometer readings, exceeded 1.8 and 2.0, respectively. This demonstrated the great potential of the herein optimized protocol to extract high-quality fungal DNA from clinical specimens enabling long-read metagenomics sequencing.IMPORTANCEA novel streamlined DNA extraction protocol was developed to efficiently isolate high molecular weight fungal DNA from hemoculture samples, which is crucial for long-read sequencing applications. By eliminating the need for labor-intensive and shear-force-inducing steps, such as liquid nitrogen grinding or bead beating, the protocol is more user-friendly and better suited for clinical laboratory settings. The automation of cleanup and extraction steps further shortens the overall turnaround time to under 6 hours. Although not specifically designed for ultra-long DNA extraction, this protocol effectively supports fungal identification through Oxford Nanopore Technology (ONT) sequencing. It yields high molecular weight DNA, resulting in longer sequence fragments that improve the number of fungal reads over human reads. Future improvements, including adaptive sampling technology, could further simplify the process by reducing the need for human DNA depletion, paving the way for more automated, bioinformatics-driven workflows.